Percepções do trabalho de psicologia do esporte em uma equipe feminina de handebol de um curso de medicina - Rami, Flávia de Oliveira Rocha (2017)
Introduction: In high-performance amateur sports, for athletes who practice them are looking for results such as victory, which means the search for skilled professionals who can train them and help them achieve their best performance is essential. The Psychology of Sports is a part of the preparation of the athletes and teams, and takes into consideration social, cultural and biological implications, among others, which can directly influence the individual’s motivation, interpersonal relationships, and well-being inside and outside the sports. Purpose: To verify the perceptions of Sports Psychology Works by identifying motivation, communication, leadership and teamwork in a women’s handball team of medical students playing in college championships. Method: A descriptive, qualitative and quantitative study of a Sports Psychology Work intervention was carried out based on a field diary, characterization questionnaires for each player, objectives and goals of handball, and motives that help with the practice of handball and focus group. A thematic analysis was conducted considering motivation, communication, leadership and teamwork. Results: Twenty-six athletes from years 1 and 6 of medical school took part in the intervention. Effectiveness of the Sport Psychology Work had confluent results in motivation, communication and teamwork. With respect to leadership, the work was not effective, influenced by university culture. Conclusion: The Sport Psychology Work was efficient for these high-performance amateur college teams and points out the need to consider both traditions and the structural, social and cultural aspects of the environment in which they are inserted. Other studies should be carried out in this direction in order to contemplate sports and modify university aspect